2016
DOI: 10.1002/jocb.171
|View full text |Cite
|
Sign up to set email alerts
|

Can Creativity Beat Death? A Review and Evidence on the Existential Anxiety Buffering Functions of Creative Achievement

Abstract: The relationship between creativity and symbolic immortality had been long acknowledged by scholars. In a review of the literature, we found 12 papers that empirically examined the relationship between creativity and mortality awareness using a Terror Management Theory paradigm, overall supporting the notion that creativity plays an important role in the management of existential concerns. Also, a mini meta‐analysis of the impact of death awareness on creativity resulted in a small‐medium weighted mean effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 79 publications
(121 reference statements)
1
11
0
Order By: Relevance
“…These findings are consistent with the TMT perspective (Vail et al, 2012) that people manage the awareness death by adhering to salient cultural worldviews (Gailliot et al, 2008;Jonas et al, 2008). Also, it is possible that cultural, but not surgical, facemasks reminded people of enduring human creativity that embodies key cultural values (e.g., beauty) in the face of death, thereby affirming people's symbolic, long-lasting existence as cultural members (Perach, 2020;Perach & Wisman, 2019). In other words, the findings of Study 3 suggest that cultural facemasks can activate terror management processes that relate to humans' unique capacity for culture (Greenberg et al, 1986), with the potential for enhancing collective resilience.…”
Section: Discussionsupporting
confidence: 75%
“…These findings are consistent with the TMT perspective (Vail et al, 2012) that people manage the awareness death by adhering to salient cultural worldviews (Gailliot et al, 2008;Jonas et al, 2008). Also, it is possible that cultural, but not surgical, facemasks reminded people of enduring human creativity that embodies key cultural values (e.g., beauty) in the face of death, thereby affirming people's symbolic, long-lasting existence as cultural members (Perach, 2020;Perach & Wisman, 2019). In other words, the findings of Study 3 suggest that cultural facemasks can activate terror management processes that relate to humans' unique capacity for culture (Greenberg et al, 1986), with the potential for enhancing collective resilience.…”
Section: Discussionsupporting
confidence: 75%
“…This includes amassing financial wealth, building families, tangible artefacts such as monuments, books, pictures or music, and intangible artefacts, such as ideas or memories ( Pyszczynski et al, 2015 ). Perach and Wisman (2019) found that creativity (related to idea generation) was associated with lower death-thought accessibility and mortality salience. Some authors have suggested that terror management theory can be used to explain consumer behaviour, such as conspicuous displays of wealth through consumption ( Arndt et al, 2004 ; Maheswaran & Agrawal, 2004 ; Rindfleisch & Burroughs, 2004 ).…”
Section: Theory and Hypothesesmentioning
confidence: 98%
“…Creativity increases upon being primed for mortality salience only if the act itself is focused on community (Routledge, Arndt, Vess, & Sheldon, 2008) or related to leaving a legacy (Sligte, Nijstad, & De Dreu, 2013). It is also notable that people with a low need for structure (which has been associated with creativity; De Jonge, Rietzschel, & Van Yperen, 2018) are less likely to be successfully primed to think about mortality salience itself (Routledge & Juhl, 2012), as are those people who reported specific evidence of creative accomplishment (Perach & Wisman, 2016).…”
Section: Terror-management Theory and Meaning-making Modelmentioning
confidence: 99%